Learn React Hooks : Build and Refactor Modern React. js Applications Using Hooks - Bugl, Daniel (Packt Publishing, Limited, 2019)
This ultimate guide on React Hooks helps you modernize managing state and effects in React apps using Hooks. You will learn various types of Hooks and how it integrates with Context and Suspense APIs. You will create custom Hooks and learn to use Hooks with Redux and MobX. Lastly, you will learn to migrate your existing React applications to Hooks.